2006
DOI: 10.3201/eid1205.051487
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus in African Wood Mouse, Guinea

Abstract: Hantaviruses are rodentborne, emerging viruses that cause life-threatening human diseases in Eurasia and the Americas. We detected hantavirus genome sequences in an African wood mouse (Hylomyscus simus) captured in Sangassou, Guinea. Sequence and phylogenetic analyses of the genetic material demonstrate a novel hantavirus species, which we propose to name "Sangassou virus."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
236
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(258 citation statements)
references
References 15 publications
3
236
1
6
Order By: Relevance
“…Ten (1.4%), 17 (2.4%), and four (0.6%) voles were seropositive to hantaviruses, LCMV, and LV, respectively (results are summarized in Table 1). RTPCRs specific for respective viruses were conducted on lung samples from individuals seropositive to hantavirus and LCMV (also some samples from seronegative voles within the same sites) (Klempa et al 2006, Vieth et al 2007, and on liver samples from individuals seropositive to LV (Donoso Mantke et al 2007). All results were negative (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Ten (1.4%), 17 (2.4%), and four (0.6%) voles were seropositive to hantaviruses, LCMV, and LV, respectively (results are summarized in Table 1). RTPCRs specific for respective viruses were conducted on lung samples from individuals seropositive to hantavirus and LCMV (also some samples from seronegative voles within the same sites) (Klempa et al 2006, Vieth et al 2007, and on liver samples from individuals seropositive to LV (Donoso Mantke et al 2007). All results were negative (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory tests indicated haematuria, elevated transaminases and thrombocytopenia and serologically confirmed HFRS. In addition, SEOV RNA was detected in her blood by nested RT-PCR [26] with 100% sequence identity (partial L segment) to Cherwell SEOV.…”
Section: Cheltenham Householdmentioning
confidence: 99%
“…2a, b), following the methodology described above. This analysis showed that MAYOV clusters within the Thailand hantavirus clade closer to the isolates circulating in the Indian Ocean, South-East Asia (Hugot et al, 2006;Plyusnina et al, 2009;Johansson et al, 2010) and Madagascar (Reynes et al, 2014), rather than the Murinae-associated hantaviruses circulating in continental Africa (Klempa et al, 2006(Klempa et al, , 2012Witkowski et al, 2014). The data suggested that both MAYOV and Anjozorobe virus, the closest variant within the Thailand hantavirus clade, may have resulted from a westward expansion of an ancestral South-East Asian hantavirus introduced with R. rattus (Cheke & Hume, 2008;Tollenaere et al, 2010).…”
mentioning
confidence: 91%
“…The following reverse transcription (RT)-PCRs were performed for hantavirus screening: (i) consensus RT-PCR using degenerate primers targeting the L gene (Klempa et al, 2006) for all samples; and (ii) specific RT-PCRs for insectivore hantaviruses targeting both the L and S segments (Kang et al, 2009) for insectivore samples. Sera from positive pooled RNA were subsequently screened independently by RT-PCR.…”
mentioning
confidence: 99%